Border basis relaxation for polynomial optimization. (May 2016) - Abril Bucero, Marta; Mourrain, Bernard
Abstract: A relaxation method based on border basis reduction which improves the efficiency of Lasserre's approach is proposed to compute the infimum of a polynomial function on a basic closed semi-algebraic set. A new stopping criterion is given to detect when the relaxation sequence reaches the infimum, using a sparse flat extension criterion. We also provide a new algorithm to reconstruct a finite sum of weighted Dirac measures from a truncated sequence of moments, which can be applied to other sparse reconstruction problems. As an application, we obtain a new algorithm to compute zero-dimensional minimizer ideals and the minimizer points or zero-dimensional G-radical ideals. Experiments show the impact of this new method on significant benchmarks.